DISCOURSE NETWORKING ANALYSIS AS ALTERNATIVE RESEARCH METHOD IN COMMUNICATION SCIENCE STUDIES - Bayu Indra Pratama; Adinda Ardwi Illahi Ulfa (Jurnal Penelitian Komunikasi dan Opini Publik, 2017)
AbstrakFokus tulisan ini ditujukan untuk menjelaskan discourse networking analysis sebagai salah satu metode penelitian yang bersifat terbuka dan dapat diterapkan dalam penelitian di bidang lain selain ilmu politik. Sejauh ini, penerapan discourse networking analysis lebih banyak digunakan dan terbatas pada kajian mengenai ilmu politik. Discourse networking analysis memungkinkan untuk diterapkan dalam bidang keilmuan lain karena memiliki dasar sama dengan social neworking analysis, misalnya dalam ilmu komunikasi. Discourse networking analysis merupakan perkembangan metodologis dari social networking analysis yang menggabung dua unsur metode yaitu analisis isi kualitatif serta analis jaringan sosial.  Sedangkan social networking analysis menjadi metode yang bersifat multidisiplin dan telah banyak digunakan dalam bidang kajian lain selain ilmu komunikasi. Untuk itu, discourse networking analysis dapat menjadi salah satu tawaran dalam kajian ilmu komunikasi.Kata kunci :  discourse networking analysis, social network analysis, metode penelitian AbstractThe main aim of this writing was focused on the Discourse Networking Analysis explanation as one of the transparent analysis method and applicable for another research domain beyond political studies. As far as it applied, the Discourse Networking Analysis was frequently applicated and limited on political discourse. The Discourse Networking Analysis was enable to be applied for another study branch because it basically similar with Social Networking Analysis, for example, it could be applied on Communication studies. The Discourse Networking Analysis was methodological development of Social Networking Analysis which combined double method elements, that is Qualitative Content Analysis and Social Network Analysis. Whereas, Social Networking Analysis has become multi-discipline methods and much more applied for another study branches beyond communication Studies. As a result, the Discourse Networking Analysis was among optional offers which Communication Studies could be presented.Keywords: discourse networking anaysis, social networking analysis, methods research